A review of behavioral interventions to enhance sports performance†. (18th March 2019) - Schenk, Merritt; Miltenberger, Raymond
Abstract : Research on applied behavior analysis and sports performance has become an increasingly popular subject. It involves using behavioral measures to assess the utility of numerous interventions to enhance athletic performance. We identified 101 studies published since the late 1960s focusing on behavioral interventions to enhance sports performance. To determine the breadth of the current research, we identified each sport and the different interventions used to improve performance. Of the studies included in this review, research has investigated 23 interventions with 21 sports. The purpose of this paper is to review the current literature regarding what procedures have been evaluated, the results of this research, some of the limitations, and future directions of behavioral research on sports performance enhancement. In doing so, this review will allow readers to easily browse the current literature by the sport or intervention of interest.